2019
DOI: 10.3800/pbr.14.189
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic divergence in viviparid snails in a recently converted freshwater lagoon

Abstract: Freshwater mollusks often show high intraspecific variability in shell morphology, which may cause incongruences between molecular phylogeny and morphology-based species taxonomy. However, it remains unclear how morphological variations in freshwater snails are associated with different habitats such as rivers, ponds, and lakes. In the present study, we investigated the morphological variation in the shells of the viviparid freshwater snail Sinotaia quadrata in the Kahoku Lagoon in Japan, which was converted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…material 1 ). In particular, the adult shell width tends to be relatively smaller than that of other Japanese Viviparidae ( Masuda and Uchiyama 2004 ; for example, under 24 mm except for one exception in Kagawa et al (2019) ).…”
Section: Taxon Treatmentsmentioning
confidence: 85%
See 1 more Smart Citation
“…material 1 ). In particular, the adult shell width tends to be relatively smaller than that of other Japanese Viviparidae ( Masuda and Uchiyama 2004 ; for example, under 24 mm except for one exception in Kagawa et al (2019) ).…”
Section: Taxon Treatmentsmentioning
confidence: 85%
“…The distinctive (see diagnosis and taxon discussion) shell morphology of H. longispira is considered to be a consequence of adaptation to its ancient lake habitat and this evolutionary change in morphology may have originated multiple times, based on examination of fossil specimens ( Hirano et al 2019b ). Furthermore, plastic and/or adaptive morphological changes to the environment seem to occur easily both within and amongst species in viviparid gastropods ( Hirano et al 2019b , Kagawa et al 2019 , Stelbrink et al 2020 ). Such morphological changes might have occurred in those H. japonica that have the elongated shell shape, as two of the three localities from where these specimens were collected are large lakes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our results showed multiple diversifications of shell morphology in Lake Biwa. Previous studies have suggested that shell morphology might be associated with habitat (Kagawa, Saito, Uchida, & Chiba, ; Miura et al, ), and the habitat of Heterogen sp. is clearly different from the habitat of H. japonica and H. longispira .…”
Section: Discussionmentioning
confidence: 98%
“…is found on the 7 m down of the rocky shore of Chikubushima Island in Lake Biwa (Hirano et al 2019). In addition, shell morphologies of viviparid snails easily change under the influence of the environment even within species [individuals of Sinotaia quadrata histrica (Gould, 1859) sampled in the lagoon had thicker and more elongated shells with narrower apertures than those sampled outside of the lagoon (Kagawa et al 2019)]. 1.2 Ma, Lake Biwa was shallower than it is in the present day (Miura et al 2019).…”
Section: Discussionmentioning
confidence: 99%